Geoprocessamento aplicado na determinação das áreas de preservação permanente e áreas de conflito com cultivo agrícola no município de Lençóis Paulista/SP - Mileski, Milena Montanholi; Campos, Sérgio [UNESP] (EIA Energy in Agriculture, 2012)
The city of Lençóis Paulista has a great part of its agricultural land cultivated by sugar cane and reforestation of eucalyptus and pine trees. In the county there are industries that exploit energy extracted from energy cogeneration. The city of Lençóis Paulista, in recent years, has been demonstrating considerable levels of economic and social growth with the industries that are working with sugarcane and eucalyptus mainly responsible. However, the expansion of agricultural land in many cases does not take into consideration the permanent preservation areas that are protected by the law. The APP's are of fundamental importance in the management and conservation of the environment preserving the natural plants and wildlife, and also preventing erosion and the silting of drainage networks. This objective of this study was to diagnose land use, analyze if Permanent Preservation Areas are regulated to the Brazilian Forestry Code (1965) and also diagnose areas of conflict. In relation to the use and occupation of land, the research has shown how the land is divided (agricultural crops and urban zones), and highlighted areas of conflict with the Permanent Preservation Areas. All of the information is contained in maps using Geographic Information Systems. However, it has become clear that environmental laws are not respected as much in urban areas as they are in rural areas. The PPA's are virtually nonexistent, thus creating damage to the environment and local population.

O município de Lençóis Paulista possui grande parte de suas terras agrícolas cultivadas com cana-de-açúcar e reflorestamentos de eucalipto e pinus. No município estão localizadas indústrias que aproveitam energia proveniente de cogeração de energia. O município de Lençóis Paulista, nos últimos anos, vem apresentando consideráveis índices de crescimento econômico e social e as indústrias que trabalham com cana de açúcar e eucalipto são algumas das responsáveis. No entanto, a expansão da fronteira agrícola, em muitos casos não tem levado em consideração as áreas de preservação permanente protegidas por lei. As APP’s são de fundamental importância para o manejo e conservação do meio ambiente, preservando a fauna e a flora e evitando erosão e assoreamento de redes de drenagem. O presente trabalho teve como objetivo diagnosticar o uso do solo, analisar se as Áreas de Preservação Permanente estão regulares de acordo com o Código Florestal Brasileiro (1965) e diagnosticar as áreas de conflito. Em relação ao uso e ocupação do solo, a pesquisa demonstrou como o solo está dividido (culturas agrícolas e zona urbana), bem como destacou as áreas de Preservação Permanente e áreas de conflito. Todas essas informações estão contidas em mapas elaborados através de Sistema de Informações Geográficas. No entanto, ficou claro que as leis ambientais são pouco respeitadas, pois tanto na área urbana como na área rural, as APP’s são praticamente inexistentes, gerando assim danos ao meio ambiente e a população local.
Geo-processing applied in determining the permanent preservation areas and areas of conflict with agricultural land and the municipality of Lençóis Paulista/SP
Keywords: Agriculture; Energy; Environment; Eermanent preservation areas; Agricultura; Energia; Meio ambiente; Áreas de preservação permanente